The Philosophy of Not Forgetting in Miloš Crnjanski’s “A Novel of London” - Filipov Radulović, Sofija D. (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The pessimistic gradation from Migration and The Second Book of Migration to A Novel of London gives reason to think that Miloš Crnjanski’s last novel can be seen as a final migration, a displacement, in which there is no star to follow, no consolation in the view of the sky or in a smile, or in an officer’s duty, which is performed even when it is no longer possible to regain the golden age. The prince’s essential belonging and marking by the country and tradition in which he was born incapacitates him to realize his existence anywhere except in the place from where he was relocated. Remaining faithful in the new world to what has passed, Rjepnin remains increasingly alone. Living in memories and the past prevents the prince from existing – in the true sense of the word – in the present, because what was once prevails over all temporal aspects of his life. Therefore, in this paper, we will talk about the impossibility of forgetting the homeland in A Novel of London.